3D seismic processing of crooked line 2D data in the vicinity of the COSC 2.5 Km deep scientific borehole - Juhlin, Christopher; Hedin, P. (EAGE Publishing BV, 2014)
Two crooked line 2D seismic profiles were acquired in the vicinity of the location of the first scientific borehole of the Collisional Orogeny in the Scandinavian Caledonides (COSC) project. The planned depth of the borehole is 2.5 km and drilling will start in mid-Spring 2014. The data were previously processed in 2D and the borehole was located based on the results of this processing. In order to obtain a better image of the subsurface and provide better predictions of the expected lithology at depth the data have been reprocessed as a sparse 3D data set. The 3D processing suggests that a larger mafic lense is expected to be penetrated at about 1000 m depth and the base of a high grade metamorphic unit at about 2.2-2.3 km depth. The upper 500 m is not well imaged due to the acquisition geometry.